STRUCTURAL CONTROLS ON TERTIARY OROGENIC GOLD MINERALIZATION DURING INITIATION OF A MOUNTAIN BELT, NEW ZEALAND - Craw D.; Begbie M.; Mackenzie D. (My University, 2006)
Two types of structurally controlled hydrothermal mineralization have occurred during folding of fissile schist in southern New Zealand: fold-related mineralization and normal fault-related mineralization. Both types have the same mineralogy and textures, and are dominated by quartz–ankerite veins and silicified breccias with ankeritic alteration. Most mineralized zones are thin (centimetre scale), although host schist is commonly impregnated with ankerite up to 20 m away. Thick (up to 5 m wide) mineralized zones are generally gold-bearing and contain pyrite and arsenopyrite with stibnite pods locally. Some of these auriferous zones have been extensively mined historically despite rugged topography and difficult access. Mineralization occurred during regional tectonic compression in the initial stages of development of the Southern Alps mountain belt at the Pacific–Australian plate boundary in the Miocene. Most of the gold-bearing deposits occur in east to south-east, striking normal faults that cut across mesoscopic folds in a belt that coincides with the southern termination of a regional-scale north trending antiform. Mineralized zones have similar structural control and relative timing to a nearby swarm of Miocene lamprophyre dykes and carbonatites. Limited stable isotopic data (C and O) and trace element geochemistry suggest that there was probably no genetic link between the igneous activity and gold mineralization. However, these two types of fluid flow have been controlled by the same tectonically created crustal plumbing system. This Miocene hydrothermal activity and gold deposition demonstrates that orogenic (mesothermal) mineralization can occur during the inception of an orogenic belt, not just in the latter stages as is commonly believed. These Miocene structures have been preserved in the orogen because the locus of uplift has moved northwards, so the early-formed gold deposits have not yet been structurally overprinted or eroded.
Keywords: GOLD; LAMPROPHYRE; OROGENIC; MESOTHERMAL; HYDROTHERMAL; TECTONIC; FOLD; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен